Solidarity Economy Markets as “mobilizational commons”: re-signifying the market through the lens of cooperation - Esteves, A. (Midi du DVLP/CRIDIS/GRIAL, 2021)
Central to “solidarity economy” is the development of parallel economic spatialities, made of “autonomous and intermediary public spaces” (Laville & Eynaud 2019: 60) where “socio-ethical and counter-cultural practices” are experimented with, enacted and coordinated (Fois 2019: 108). A balancing act embedment of their activities in cooperative norms and practices mobilizing support from mainstream society and its institutions Build economic and political alliances, while embedding economic activity in counterhegemonic norms and practices.